2014
DOI: 10.2147/ndt.s66941
|View full text |Cite
|
Sign up to set email alerts
|

The Yamaguchi fox/pigeon-imitation test, a brief cognitive performance rating tool, in a community-dwelling population: normative data for Japanese subjects – a preliminary study

Abstract: IntroductionScreening tools for dementia should be valid and easy to complete and have a low psychological burden. Consistent with these principles, the Yamaguchi fox/pigeon-imitation test (YFPIT) has been developed. However, there is little information on the utility of the YFPIT for preclinical populations, although the detection of proven prodromal and preclinical states is important.Materials and methodsWe recruited 392 volunteers who were at least 60 years old (139 men and 253 women) and had participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…Overall, the sensitivity of the pigeon finger imitation test was 44%, which was close to that reported by Ishioka et al (43.8%, n = 16). They also reported that the female dementia patient group had a significantly higher failure rate in the pigeon-finger imitation test (5), but the present results showed no statistically significant sex difference. Ishioka et al also reported that DLB had a higher success rate in the pigeon-finger imitation test than AD; however, the present study results showed that DLB had a significantly higher failure rate (p = 0.0274, Fisher's exact test).…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Overall, the sensitivity of the pigeon finger imitation test was 44%, which was close to that reported by Ishioka et al (43.8%, n = 16). They also reported that the female dementia patient group had a significantly higher failure rate in the pigeon-finger imitation test (5), but the present results showed no statistically significant sex difference. Ishioka et al also reported that DLB had a higher success rate in the pigeon-finger imitation test than AD; however, the present study results showed that DLB had a significantly higher failure rate (p = 0.0274, Fisher's exact test).…”
Section: Discussioncontrasting
confidence: 76%
“…The second limitation, as previously pointed out by Yamaguchi et al, is that the fox finger imitation test has a low sensitivity for screening dementia patients ( 4 ). To the best of my knowledge, only one study in Japan has compared the fox finger and pigeon finger imitation tests ( 5 ). In the present study, 25 of the 51 patients who underwent the fox finger imitation test also underwent the pigeon finger imitation test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation